MO509DOSE-RESPONSE RELATIONSHIP BETWEEN ALCOHOL CONSUMPTION AND THE RISK OF DEVELOPING CKD: RETROSPECTIVE COHORT STUDY. (29th May 2021) - Hashimoto, Yusaku; Imaizumi, Takahiro; Hori, Akihiro; Kato, Sawako; Yasuda, Yoshinari; Maruyama, Shoichi
Abstract: Background and Aims: Drinking habits are one of the most important modifiable lifestyle factors to prevent the development of chronic kidney disease (CKD). Previous studies showed that it was inversely associated with the risk of developing CKD, but the dose-response relationship between alcohol consumption and the development of CKD is still controversial. In the present study, we aimed to examine whether the amount of alcohol consumed at one time is associated with new onset of CKD in general population. Method: Study subjects were 11, 162 Japanese aged 45 to 74 years, with an estimated glomerular filtration rate ≥60 mL/min/1.73m2, no proteinuria, no past history of cardiovascular disease, COPD or liver disease. The drinking status was obtained by self-administered questionnaires. We categorized the study subjects into four groups based on the amount of alcohol consumption: <20g/time of ethanol equivalent (lowest); 20-40g/time (low intermediate); 40-60g/time (high intermediate); >60g/time (highest). We set non-drinkers as a reference category. The primary outcome was the incidence of CKD, defined as 25% reduction of eGFR and to less than 60 mL/min/1.73 m2 and/or a dipstick urinalysis score of 1+ or greater (equivalent to ≥30 mg/dL) during the follow up period. We employed Cox proportional hazards regression models to examine the dose-response relationship between baseline alcohol consumption and the risk of CKD. Trend tests were performed using Cox proportional hazards regression models that treated alcohol consumption as a continuous linear term. Results: Lowest and low intermediate groups were significantly associated with a decreased risk of CKD (hazard ratio [HR] 0.84; 95% confidence interval [CI], and 0.71–0.99; HR 0.79; 95% CI, 0.66–0.96, respectively) compared to non-drinkers. High intermediate group was associated with a decreased risk of CKD (HR 0.92; 95% CI, 0.70–1.21), and highest group was associated with an increased risk of CKD (HR 1.28; 95% CI, 0.84–1.95), but these associations did not reach statistical significance. There was no dose-response relationship between baseline alcohol consumption and risk of CKD (P-trend = 0.30). Conclusion: A J-shape association was observed between self-reported alcohol intake and the incidence of CKD. Moderate alcohol consumption at one time may help reduce the risk of CKD.